HALF-CENTURY COLLABORATION. 75 YEARS OF RUSSIAN STUDIES AT THE UNIVERSITY OF Ss. CYRIL AND METHODIUS IN SKOPJE. 50 YEARS OF MACEDONIAN STUDIES AT LOMONOSOV MOSCOW STATE UNIVERSITY (Philological Studies, 2025)
The article presents material on the 50 years of cooperation between the Philological Faculty of the Lomonosov Moscow State University and the Ss. Cyril and Methodius University in Skopje, the main centers of Macedonian studies in Russia and Russian studies in Macedonia. The emphasis is on the fact that during half a century of teaching Macedonian language and literature at Moscow State University (since 1975) and over 75 years of studying Russian language and literature at the University in Skopje, joint textbooks have been written, dictionaries have been published, lecturers have been exchanged, students have been participating in Summer Schools, and internships have been awarded to write bachelor's, master's and doctoral theses. Furthermore, there has been fundamental research conductedprepared and dissertations defended, as well as publication of monographs and numerous articles on Macedonian studies, Russian studies and Russian-Macedonian linguistic and literary relations. Finally, there is also the organisation of joint scientific conferences, while at the same time both faculties are working on the implementation of new projects.
Keywords: Philological Faculty of Lomonosov Moscow State University, Philological Faculty „Blaže Koneski“ University of Ss. Cyril and Methodius in Skopje, Macedonian language, Macedonian literature, Russian language, Russian literature, literary connections, cultural connections, scientific connections